Strategi pemasaran jasa transportasi taksi konvensional menghadapi persaingan jasa transportasi berbasis aplikasi online di Surabaya - Dwi Karya Yuris Prabawati; Soni Harsono (Journal of Business & Banking, 2017)
This research analyzes and explains the application of conventional taxi marketing strategy of Blue Bird in face of online application based transportation competition in Surabaya Indonesia. This research uses qualitative phenomenological approach. Data were collected from the operational and marketing managers of Blue Bird taxi (1 person), the driver (10 persons), and customer (10 people). To obtain complete information has been done observation, documentation, and interviews with open questions. The results show that Blue Bird's taxi marketing strategy consists of services, prices, distribution, promotion, people, physical evidence and processes that can impact on the company's performance is still not running well in the face of competition of online application-based transportation services. In terms of distribution strategies, people, physical evidence, and processes have been excellent but in product strategy, service, pricing, and promotional strategies are still in a weak condition. The implication of this research is that Blue Bird companies can improve their service innovation primarily on technology aspects, and then lower tariffs for consumers, and lastly use the internet medium to improve efficiency and cheaper than others so as to compete with online-based applications transportation services in Surabaya.